Impact of sympathetic dysfunction in the etiology of overactive bladder in women: A preliminary study. Issue 1 (11th August 2014) - Ates, Erhan; Ipekci, Tumay; Akin, Yigit; Kizilay, Ferah; Kukul, Erdal; Guntekin, Erol
Abstract : Aims: We investigated the effects of autonomic sympathetic dysfunction in the etiology of overactive bladder (OAB) in women, by assessing the sympathetic skin response (SSR). Methods: In total, 40 women with OAB and 15 volunteers were enrolled. Group 1 (n = 20) consisted of patients who benefitted from oral anticholinergics, Group 2 (n = 20) consisted of patients who were refractory to oral anticholinergics, and the volunteers (n = 15) were the control group. All patients were asked to complete OAB‐SF questionnaires. The absence of SSR was accepted as significant. Detailed physical examinations including neurological examinations were performed. All patients underwent SSR tests on the skin of the hands, feet, and genital area in our neurology department using electromyography, and SSR responses were recorded. Statistical significance was accepted at P  < 0.05. Results: The mean age was 47.2 ± 12.4 years. In total, 55 women were evaluated (20 in Group 1, 20 in Group 2, and 15 in the control group). Mean OAB scores were similar between groups 1 and 2, although urgency was significantly higher in Group 2 than 1. The absence of SSR was significantly higher in Group 2 than 1 ( P  = 0.01). Impaired SSR was observed more commonly in Group 2 than 1. All controls had normal SSRs. Conclusions: Regional dysfunction in the autonomic nervous system may be part of OAB's etiology. SSR may be a candidate test for determining early OAB, and may also be useful for predicting antimuscarinic‐refractory patients. Neurourol. Urodynam. 35:26–28, 2016 . © 2014 Wiley Periodicals, Inc.